Prognostic Value of EZH2 in Non-Small-Cell Lung Cancers: A Meta-Analysis and Bioinformatics Analysis. (9th November 2020) - Fan, Kui; Zhang, Chuan-long; Qi, Yuan-fu; Dai, Xin; Birling, Yoann; Tan, Zhao-feng; Cao, Fang
Abstract : Background . The prognosis of non-small-cell lung cancer (NSCLC) has not been significantly improved. In the past several years, research on epigenetics is in full swing. There is a focus on the gene EZH2; however, its role as a predictor of the prognosis of NSCLC is in the debate. Objective . To clarify if the expression level of EZH2 can influence the prognosis of NSCLC and explain its prognostic value. Methods . We have systematically searched PubMed, Web of Science, and Cochrane library, screened relevant articles, and conducted a meta-analysis on the expression level of EZH2 in NSCLC. We collected the hazard ratio (HR) and the 95% confidence interval (CI) and used STATA 12.0 to calculate the combined result of EZH2 overall survival. In addition, we conducted subgroup analyses, a sensitivity analysis, and a funnel plot to test the reliability of the results. We further validated these meta-analysis results using the Kaplan-Meier plotter database and The Cancer Genome Atlas (TCGA) database. In addition, we have investigated the correlation between EZH2 expression and EGFR expression, KRAS expression, BRAF expression, and smoking in TCGA database to further explore the mechanism behind the influence of high EZH2 expression on lung cancer prognosis. Results . 13 studies including 2180 participants were included in the meta-analysis. We found that high expression of EZH2 indicates a poor prognosis of NSCLC (HR = 1.65 and 95% CI 1.16-2.35; p ≤ 0.001 ). Subgroup analyses showed high heterogeneity in stages I-IV (I 2 = 85.1 % and p ≤ 0.001 ) and stages I-III (I 2 = 66.9 % and p = 0.029 ) but not in stage I (I 2 = 0.00 % and p = 0.589 ). In the Kaplan-Meier plotter database, there was a high expression in 963 cases and low expression in 964 cases (HR = 1.31 and 95% CI 1.15-1.48; p < 0.05 ). Further analysis found that the high expression of EZH2 was statistically significant in lung adenocarcinoma (HR = 1.27 and 95% CI 1.01−1.6; p = 0.045 ), but not in lung squamous cell carcinoma (HR = 1.03 and 95% CI 0.81−1.3; p = 0.820 ). The results of the TCGA database showed that the expression of EZH2 in normal tissues was lower than that in lung cancer tissues (p < 0.05 ). Smoking was associated with high expression of EZH2 (p < 0.001 ). EZH2 was also highly expressed in lung cancers with positive KRAS expression, and the correlation was positive in lung adenocarcinoma (r = 0.3129 and p < 0.001 ). The correlation was also positive in lung squamous cell carcinoma (r = 0.3567 and p < 0.001 ). EZH2 expression was positively correlated with BRAF expression (r = 0.2397 and p < 0.001 ), especially in lung squamous cell carcinoma (r = 0.3662 and p < 0.001 ). In lung squamous cell carcinoma, a positive yet weak correlation was observed between EZH2 expression and EGFR expression (r = 0.1122 and p < 0.001 ). Conclusions . The high expression of EZH2 indicates a poor prognosis of NSCLC, which may be related to tumor stage or cancer type. EZH2 may be an independent prognostic factor for NSCLC. EZH2 high expression or its synergistic action with KRAS and BRAF mutations affects the prognosis of non-small-cell lung cancer.